A nanosecond Q-switched fiber laser based on step-index multimode fiber. (25th June 2021) - Li, N; Guo, M; Zhang, W Y; Zhang, J; Guo, Z X; Zheng, T Q; Li, Y Z; An, S R; Song, L J
Abstract: A nanosecond passively Q-switched fiber laser using a single mode-step-index-multimode-single mode fiber (SMF–SIMF–SMF) device as the saturable absorber (SA) is demonstrated. Such SMF–SIMF–SMF device operates based on nonlinear multimode interference. A stable Q-switched erbium-doped fiber laser at 1546 nm was realized with a repetition rate varying from 99 kHz to 150 kHz and the shortest pulse duration of 740 ns. At the maximum pump power of 800 mW, the maximum pulse energy of 97.86 nJ at an average output power of ∼14.7 mW was obtained. Our results indicate that the SMF–SIMF–SMF structures can be used as effective SAs for nanosecond pulse generation.